Key Molecules and Pathways Underlying Sporadic Amyotrophic Lateral Sclerosis: Integrated Analysis on Gene Expression Profiles of Motor Neurons - Lin, Jianing; Huang, Pian; Chen, Weineng; Ye, Chenghui; Su, Huanxing; Yao, Xiaoli (Frontiers in Genetics, 2020)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by progressive loss of motor neurons. The complex mechanisms underlying ALS are yet to be elucidated, while the lack of disease biomarkers and therapeutic options results in the poor prognosis of ALS patients. In this study, we performed integrated bioinformatics analysis to clarify potential mechanisms in sporadic ALS (sALS). We compared three gene expression profiles (GSE18920, GSE56500 and GSE68605) of motor neurons obtained from sALS patients and healthy controls to discover differentially expressed genes (DEGs), and then performed integrated bioinformatics analyses to identify key molecules and pathways underlying sALS. We found that these DEGs were mainly enriched in extracellular matrix components and cell adhesion. The clustered subnetwork of the constructed protein-protein interaction network for DEGs and the group of selected hub genes were both significantly involved in extracellular structure organization and endoplasmic reticulum lumen. The transcriptional factors database proposed RelA and NF-κB1 from NF-ĸB family, as well as Twist1 and Twist2 from Twist family as the key regulators of the hub genes. These results demonstrate the alternations of extracellular matrix and cell adhesion in motor neurons and suggest several regulatory pathways in the pathogenesis of sALS.